MOECHTAZAR M PADA MASA PRRI DAN KETERLIBATAN DALAM BIDANG INSTANSI KESEHATAN (INKES) 1956-1960 - -, SARJAN - (Pendidikan Sejarah, 2014)
This  study  exposes  Muchtazar  M:  his  role  at  PR.RI   prior  time  in  Health Foundation (INKES) department 1956 - 1960. Moechta zar M was born on July 30" 1930 from the couple Muhammad Nur with Marcliah. B.orn in the ordinary family. The role of Moechtazar M in Health Foundation (INKES) was Technical Operation Units. The forgotten members ·of Health Foundation ,(lNKES) that makes b(!ckground to write Moecchtazar M biography at PRRI prior ti e and his role in the Health Foundation (INKES) 1956- 1960. This research uses historical method "vith steps. Heuristic, Sources Critical, and Intepretation. This study result shows that Moechtazar M role during in the Health Foundation (INKES) and joined with PMI undcrcommand of Capten Gunawan 1956 - 1960 that had an important role, during his concerning in the Health Foundation (INKES) be had successfully done his responsibility to serve people and nation. Moechtazar M gave new knowledge to people that were dulls at the colonialism era. The conclusion of this study is Moechtazar M was born in the ordinary family on the small village named Sungai Tarab in Batusangkar regency. His occupation was as a member of the Health Foundation (INKES) 1956 - 1960. He is a good figure and good to be followed for his discipline and high responsibility toward family and friends. He is also an alive witness for nows young generation who wants to know the West Sumatrans struggle in the colonialism to get the independence and after the independence struggle.